X [videorecording (DVD)] - West, Ti, 1980-; Goth, Mia, 1993-; Ortega, Jenna; Henderson, Martin, 1974-; Snow, Brittany, 1986-; Campbell, Owen (Actor); Ure, Stephen, 1958-; Mescudi, Scott, 1984- (Lionsgate, 2022)
In 1979 some young filmmakers set out to make an adult film in rural Texas, but when their reclusive, elderly hosts catch them in the act, the cast members find themselves in a fight for their lives.